Permanent Demand and Private Investment in the General theory: an empirical investigation - Jose A. Pérez Montiel; Carles Manera Erbina (Revista de Economía Mundial, 2020)
We empirically test some Keynes’ (and post Keynesians’) assertions relative to the multiplier-accelerator principle. By means of the nonlinear causality test proposed by Diks and Wolski (2016), we conclude that in the United States domestic private investment is driven by permanent demand. We explain that this result is consistent with Keynes’s principle of effective demand in the long run. We hope this paper helps consolidating the potential consensus among Keynesian, Kaleckian and Sraffian economists initiated by the work of Allain (2015).